The Influence of Social Media Marketing on Consumer Based Brand Equity, Brand Loyalty, and Mediation by Brand Experience on Fashion Brand Clothing in Indonesia - Dimas Aditya Syahputra; Kurniawati (Indonesian Journal of Economic & Management Sciences, 2023)
The purpose of this research is to examine the effect of social media marketing initiatives on brand equity and brand loyalty through brand encounters. 205 participants made a purposive sampling sample for this study. The consumers who were the samples of this study, among others, had bought local fashion brands in Indonesia for at least the last six months. Hypothesis testing was carried out using the structural equation model (SEM) method with the help of AMOS software. For further research, it is also possible to add and analyze additional factors that strengthen local fashion brands that are influenced by brand recognition and image building are two examples of social media marketing activities